Transcriptionally active c-myc oncogene is contained within NIARD, a DNA sequence associated with chromosome translocations in B-cell neoplasia - Marcu, Kenneth B. (1983)
NIARD (non-immunoglobulin-associated rearranging DNA) is located on mouse chromosome 15 at the break point of a commonly observed translocation event involving chromosomes 15 and 12 in murine plasmacytomas. The human cellular analogue of the v-myc oncogene of avian myelocytomatosis virus, strain MC-29, is known to reside on the distal end of human chromosome 8 and has been observed to translocate to chromosome 14 in Burkitt lymphomas. Using a cDNA clone specific for the transcript of the human c-myc gene (H c-myc), we show that the mouse c-myc (M c-myc) gene is contained within NIARD. NIARD-associated chromosome translocations occurred 1.3-2 kilobases (kb) 5′ of the mouse c-myc gene where NIARD recombines with the switch region of the C(α) immunoglobulin gene in various murine plasmacytomas. The mouse c-myc encoding region within NIARD spanned <2.4 kb of DNA and expressed a low level of a 2.3-kb polyadenylylated RNA in BALB/c spleen. Increased (10- to 20-fold) levels of rearranged mouse c-myc transcripts (i.e., ≈1.8-2.1 kb) were observed in plasmacytomas that have NIARD-associated chromosome translocations. Human c-myc and NIARD probes detected DNA rearrangements of human c-myc in four of seven Burkitt lymphomas. DNA sequences adjacent to the human c-myc gene recombined with the C(μ) immunoglobulin gene locus on chromosome 14 in several Burkitt lymphomas. The activation of the c-myc oncogene by chromosome translocation implicates its involvement in B-cell oncogenesis.